Grammatical Cohesive Devices Analysis In Descriptive Writing By English Department Students In Putera Batam University - Robby Satria; Nurma Dhona Handayani (LPPM Universitas Putera Batam, 2018)
This research has purpose to discuss about linguistics that related to discourse analysis. In this aspect discusses the analysis of language use in texts. The phenomena of discourse analysis can be seen in the usage of cohesion. The concept of cohesion relatively uncommon to many people. Sometimes people fail in making a cohesive writing. It also happens to the students, especially English Department students. They often find a mistake in determining the concept refers to relations of meaning and context that exist within the text. Cohesion is considered as one of the most important aspect in the analysis of text discourse that needed to be understood by English learners especially English Department students. The ability of using grammatical cohesive devices determines student’s capability in writing. In this research, it is found that students have ability in using grammatical cohesive devices such as: Reference, Substitution, Ellipsis and Conjunction. The percentage of each device indicates their knowledge toward grammatical cohesive device in writing descriptive text. In addition, the result of this research also classified the types of cohesion found in descriptive writing by English Department students in Putera Batam University. Result of this research, students are not taught grammatical cohesive devices, they are asked to write a text where it is supposed to be cohesive in the use of the different types of grammatical cohesive devices. The conclusion we got from the analysis of the students’ test was that students use quite enough grammatical cohesive devices in their writing. But, most of them are confuse and it seems that the inappropriate use of grammatical cohesive devices is concerned with some of them as conjunctions which are most commonly used.